PKM Asesmen Siswa SLB Paedagogia Maospati pada Pelatihan Laminasi Triplek untuk Komponen Kursi dan Meja - Maria Widyastuti; Stefanus Prabani Setio (GUYUB: Journal of Community Engagement, 2023)
This assessment was carried out when SLB Pedagogia Maospati students in Magetan Regency practiced skills in making table and chair components using plywood lamination techniques. Training is carried out in seven stages of the production process. Twelve male and female students with three disabilities, namely mental impairment, hearing impairment and physical impairment. The training method is carried out on practice, by carrying out work examples and practicing them directly by students. After the training is complete, an assessment is carried out on students for each stage that has been trained. Assessment is carried out in two methods, namely: 1) qualitative by writing down what activities students can carry out; 2) Quantitatively, students will be assessed for their abilities on an assessment scale that has a range of Not Capable with a score of 1, and Very Capable with a score of 7. The aim of this assessment is to group students in the existing production process. This is intended so that students have the ability and can develop it into a production process that can be carried out. The conclusion of the implementation of Community Service resulted in eight Faktors that influenced SLB students to accept the knowledge transfer provided by the UKDC PkM Team in 2023.